Restandardisation defined as democratising language planning - Odendaal, Gerda (Stellenbosch Papers in Linguistics Plus, 2014)
The 1980s and 1990s saw several international political and social developments that gave rise to the ideology of democracy, which focuses on issues such as equal human rights and human dignity. Furthermore, globalisation gave rise to a worldwide ethnic renaissance with a focus on the nurturing of diversity. These developments led to the increased valuing and validation of variation, including language variation. Given this democratisation of the world, the relevance of standard languages, which are undeniably ideological in nature, is increasingly being questioned. Does a language variety which only serves the economic, social and political elite of a speech community still have a role to play in a democratic society? Or should we accept that this will inevitably lead to the destandardisation of languages? These are the questions that gave rise to discussions on the restandardisation of languages. The literature is, however, not yet clear on what is meant by restandardisation, as no unambiguous definition of this term exists as of yet. The aim of this paper is to give a clearer understanding of what restandardisation entails by discussing relevant literature on restandardisation, standardisation, destandardisation and other aspects of language planning in order to provide an unambiguous definition of restandardisation. By specifying its language planning and democratic properties, this paper aims to define restandardisation as democratising language planning, i.e. a language planning activity with the ability to transform the standard language in order to make it a democratic tool of communication that serves the entire speech community and in which all the speakers of the different varieties of a language are represented.